Pharmacokinetic Analysis of an Isoniazid Suspension Among Spanish Children Under 6 Years of Age - Antoni Noguera-Julian; Emma Wilhelmi; Maria Cussó; Rob Aarnoutse; Angela Colbers; Loreto Martorell; Maria Goretti López-Ramos; Joan Vinent; Rosa Farré; Dolors Soy; Sílvia Simó-Nebot; Clàudia Fortuny (Antibiotics)
Background: Isoniazid (INH) remains a first-line drug for the treatment of tuberculosis (TB) in young children. In 2010, the WHO recommended an increase in the daily dose of INH up to 10 (7–15) mg/kg. Currently, there are no INH suspensions available in Europe. Methods: We aimed to characterize the pharmacokinetics of a licensed INH suspension (10 mg/mL, Pharmascience Inc., Montreal, QC, Canada) in children receiving INH daily at 10 mg/kg in a single-center, open-label, non-randomized, phase IIa clinical trial (EudraCT Number: 2016-002000-31) in Barcelona (Spain). Samples were analyzed using a validated UPLC-UV assay. The N-acetyltransferase 2 gene was examined to determine the acetylation status. A non-compartmental pharmacokinetic analysis was conducted. Results: Twenty-four patients (12 females) were included (primary chemoprophylaxis, n = 12; TB treatment, n = 9; and TB infection preventive treatment, n = 3). The acetylator statuses were homozygous fast (n = 3), heterozygous intermediate (n = 18), and homozygous slow (n = 2; unavailable in one patient). The INH median (IQR) Cmax and AUC0–24h values were 6.1 (4.5–8.2) mg/L and 23.0 (11.2–35.4) h∙mg/L; adult targets (>3 mg/L and 11.6–26.3 h∙mg/L) were not achieved in three and six cases, respectively. Gender, age at assessment (<2 or >2 years), and INH monotherapy (vs. combined TB treatment) had no impact on pharmacokinetic parameters. Significant differences in Cmax (p = 0.030) and AUC0–24h (p = 0.011) values were observed based on acetylator status. Treatment was well tolerated, and no severe adverse events were observed; three patients developed asymptomatic mildly elevated alanine aminotransferase levels. Conclusions: In infants and children receiving a daily INH suspension at 10 mg/kg, no safety concerns were raised, and the target adult levels were reached in the majority of patients.